A Continuous Model for Multistore Competitive Location - Dasci, Abdullah; Laporte, Gilbert (Operations Research, 2005)
This paper presents a simple model to determine the location strategies of two retail firms planning to open a number of stores in a geographical market. Firms try to maximize their profit under a leader-follower type competition in which the number of stores is made endogenous by the introduction of fixed costs. A novel methodology is developed in which firms’ strategies are defined in terms of their location densities. This methodology leads to a model that is solvable analytically, and to several results on competitive location strategies. First, it is shown that if the follower decides to enter a market, he enters at least as strongly as the leader. Second, the leader can effectively deter entry even if she is severely cost-disadvantaged. However, in some cases the leader is better off by allowing the follower to enter the market. Third, the leader may also let the follower enter the market in some situations where she has a cost advantage. It is also shown that in situations where both firms enter the market, their location strategies are quite insensitive to model parameters.